DNA methylation changes during acute COVID-19 are associated with long-term transcriptional dysregulation in patients' airway epithelial cells - Messingschlager, Marey; Mackowiak, Sebastian D.; Voelker, Maria Theresa; Bieg, Matthias; Loske, Jennifer; Chua, Robert Lorenz; Liebig, Johannes; Lukassen, Sören; Thürmann, Loreen; Seegebarth, Anke; Twardziok, Sven; Dončević, Daria; et al. (EMBO molecular medicine, 2025)
Molecular changes underlying the persistent health effects after SARS-CoV-2 infection remain poorly understood. To discern the gene regulatory landscape in the upper respiratory tract of COVID-19 patients, we performed enzymatic DNA methylome and single-cell RNA sequencing in nasal cells of COVID-19 patients (n = 19, scRNA-seq n = 14) and controls (n = 14, scRNA-seq n = 10). In addition, we resampled a subset of these patients for transcriptome analyses at 3 (n = 7) and 12 months (n = 5) post infection and followed the expression of differentially regulated genes over time. Genome-wide DNA methylation analysis revealed 3112 differentially methylated regions between COVID-19 patients and controls. Hypomethylated regions affected immune regulatory genes, while hypermethylated regions were associated with genes governing ciliary function. These genes were not only downregulated in the acute phase of the disease but sustained repressed up to 12 months post infection in ciliated cells. Validation in an independent cohort collected 6 months post infection (n  = 15) indicated symptom-dependent transcriptional repression of ciliary genes. We therefore propose that hypermethylation observed in the acute phase may exert a long-term effect on gene expression, possibly contributing to post-acute COVID-19 sequelae.
Gesehen am 24.02.2026